Sedimentological study of distal rain- triggered lahars: the case of west coast of Ecuador (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In this paper we present geological evidence of secondary rain triggered lahar that affected the central coast of Ecuador in the last 2ky. Eight main ash units were described in the field and then physically and petrographically characterized in the laboratory. The units present four main kinds of deposits testifying different depositional processes and the palaeotopographic condition of these sectors of Ecuador. The deposits recognized on the field are associable with granular flows with a high amount of water that compared with similar cases in the world not exceed run-out of 40km. The lateral variation inside the deposits recognized, considering the thickness and the distance from the main Holocene volcanoes (>160km), allows us to relate with secondary rain-triggered lahars and not with primary lahars. The presence of fine-grained ash of mm to the cm-thick layer above a cm to meter thick sand to gravel layer point out that these deposits are linked with single events and not with a continuous river sedimentation process. These events were triggered by rain that remobilized distal fallout deposits linked with the last 2ka eruptive activities of the Ecuadorian volcanoes as Quilotoa, Cotopaxi and Guagua Pichincha. Several units were identified in the deposits studied, and particularly it is possible to observe in one of them lateral variations of the deposits that permit to localize the debris flow body related to the secondary rain triggered lahar. The body of the debris flow is present in the coastal sector comprise between Crucita and Jama and it shows a lateral change in lithofacies related to different palaeo topographic conditions. In conclusion, in this paper, we show how the formation of secondary rain triggered lahar can occur in the coastal sector of Ecuador principally near the main river but also in flat topographic condition. Moreover, the presence of human bones and porcelain fragments also confirms that in the past, these events strongly affected old civilizations. Different municipalities as Manta, Bahia, San Vincente, Canoa, and Jama are undoubtedly exposed today to this kind of hazard. Further researches must be focused on the evaluations of the lahar volumes that can affect the coastal area of Ecuador.